Lexical equivalence through the English-Vietnamese translation of public signs in Hanoi = Sự tương đương từ vựng qua dịch Anh –Việt của các biển báo công cộng ở Hà Nội - To, Thi Thu Huong (2020)
The fact that translation plays an essential role in every field of society can not be denied particularly in the periods of globalization. Bilingual public signs at the airport are informative instructions that travelers would pay attention to and get some information. The minor thesis is therefore into lexical equivalence through English - Vietnamese translation of words in public signs collected at the airport and The Temple of Literature in Hanoi . More specifically, translation of those public signs are analyzed under Baker (2018)’s theory framework. Through the collection and analysis of words between English and Vietnamese, non-equivalence at lexical level are found in several signs. As a result, translators would identify and analyze equivalence problems in translation process of public signs to prevent readers from misunderstanding of the message that a bilingual sign conveys. The contribution of the research is not only to boosting improvement of translation quality in the future’s bilingual public signs but becoming a precious reference document for the next researchers as well. Recommendations are proposed with regards to effective strategies in the translated bilingual signs between English and Vietnamese.